Periodontal disease during pregnancy: assessment of determinants of health and quality of life in pregnant women with periodontitis (Research, Society and Development, 2021)
Periodontitis in pregnancy may be associated with several determinants of health and knowing these determinants makes possible an integral approach of the patients. The aim of this study was to evaluate the determinants of health and periodontitis-related quality of life in pregnant women. Sample was composed by 128 patients divided into two groups: pregnant women with periodontitis (GP = 64) and without periodontitis (GWP = 64) during the third trimester of pregnancy. They were evaluated regarding: a) socioeconomic level; b) anthropometric parameters; c) systemic conditions - presence of arterial hypertension and diabetes mellitus; d) behaviors regarding oral hygiene; and e) oral health impact profile (OHIP-14). T-test, Mann-Whitney U-test, chi-square and logistic regression were applied, considering a significance level of 5%. GP showed low socioeconomic level (P = 0.0008), high maternal body mass index (BMI) (P = 0.0002) and excessive gestational weight gain (P = 0.008). No intergroup differences were observed in systemic conditions. Patients with periodontitis presented low daily dental floss use (P = 0.021) and strong impact on quality of life for all evaluated dimensions (P < 0.05). Periodontitis in pregnancy was associated with high BMI, excessive gestational weight gain, low socioeconomic level, poor oral hygiene behaviors and negative impact on quality of life.